설비공학회 분야의 최근 연구 동향 : 2017년 학회지 논문에 대한 종합적 고찰 - 이대영; 김현정; 김동선; 박준석; 임병찬 (설비공학 논문집, 2018)
This article reviews the papers published in the Korean Journal of Air-Conditioning and Refrigeration Engineering during 2017. It is intended to understand the status of current research in the areas of heating, cooling, ventilation, sanitation, and indoor environments of buildings and plant facilities. Conclusions are as follows. (1) In building mechanical system research fields, twenty studies were reported for achieving effective design of the mechanical systems, and also for maximizing the energy efficiency of buildings. The topics of the studies included energy performance, HVAC system, ventilation, renewable energies, etc. Proposed designs, performance tests using numerical methods and experiments provide useful information and key data which could be help for improving the energy efficiency of the buildings. (2) The field of architectural environment is mostly focused on indoor environment and building energy. The main researches of indoor environment are related to the ventilated cavity of curtain-wall system for enhancing insulation and preventing condensation, the improvement plans of condensation defect examples in apartment building and the calculation method for the transmitted solar irradiance using the total horizontal irradiance. The subjects of building energy are worked on the energy consumption characteristics in office buildings, energy performance analysis for energy saving potentials in a hospital building, outdoor air cooling system operated with load prediction, building energy efficiency rating changes by enhanced building envelope standards, energy saving effect for the external insulation construction, energy reduction of a heating network through the application of an absorption heat pump, analysis of thermal load profile according to the window retrofit in an old school building, calculating regional balance point temperature for heating degree-days in korea, short-term load prediction using artificial neural network models, the simple window model applied to EnergyPlus, possibility of building energy saving through the building data, optimal cooling operation of a single family house model equipped with renewable energy facility by linear programming. The remained studies are related to the comparison between korea and china evacuation laws in office building, the effect of cold air stimulation during the driver’s drowsiness, the calculation of the attached- piping-material rate for the building mechanical-service system in office buildings, the development of a modular- lightweight steel ceiling system and the evaluation of local loss coefficients for different waveguide-below-cutoff (wbc) arrays of electromagnetic pulse. (3) Various studies were published in the categories of refrigeration cycle, alternative refrigeration/energy system, system control. In the refrigeration cycle category, research subjects include the improvement of Type II and double-effect absorption heat pumps, the seasonal performance of compression heat pumps, a vertical receiver in a compression heat pump, the performance of a domestic built-in ice maker and the performance characteristics of a surface water heat pump system. In the alternative refrigeration/energy system category, subjects include a membrane dehumidification system, a CO2-hydrate circulation system, a Zeolite 13x chemical thermal energy storage system and the performance criteria for heat pumps as a renewable energy device. In the system control category, subjects include a defrosting control system using photoelectric sensors and the control method for an organic thermal storage-chiller system. (4) Research works on heat transfer area have been reviewed in the categories of heat transfer characteristics, pool boiling and condensing heat transfer and industrial heat exchangers. Researches on heat transfer characteristics included the results for prediction of stratification model for diffusers in underfloor air distribution system using the CFD, transport properties for transportation of captured CO2, dynamic thermal design of a 1-ton class bio-hydrogen production system simulator, cylindrical premixed burner, heat transfer enhancement in a divergent passage with 30° inclined ribs, the development of regulatory guideline on the applicability of CFD software, a staggered fin, single phase thermal stratification in both cold legs and downcomer. In the area of pool boiling and condensing, effects of tube diameter and surface sub-cooling temperature on R1234ze(E) and R1233zd(E) film condensation heat transfer characteristics in smooth horizontal laboratory tubes, surface energy variations and condensate behaviors on nitrogen ion implanted aluminum surfaces were studied. In the area of industrial heat exchangers, plate type enthalpy exchanger through CFD analysis of elements, fluidized bed heat exchanger for heat recovery from multi-heat sources, paper enthalpy exchange element by impregnation of the spacer, the effect of the air temperature on the air-side heat-transfer coefficient and the friction factor of a fin-and-tube heat exchanger, cooling of telecommunication cabinet, effects of seawater fouling on a plate-frame heat exchanger, carbon dioxide during heating process in the near-critical region for single channel, a heat exchanger for an air-compressor of a railway vehicle were studied.
Keywords: Thermal storage(축열); Plate heat exchanger(판형 열교환기); Membrane dehumidification(멤브레인 제습); Heat pump(히트펌프); Geothermal system(지열시스템); Geothermal heat exchanger(지중열교환기); Insulation(단열); District heating(지역난방); Air-conditioning(공조); Building energy(건물에너지); Low energy house(저에너지주택); Floor heating(바닥난방); Ventilation(환기); Absorption chiller(흡수식 냉동기); Fouling(파울링)